Checklist, typifications, and nomenclatural notes on Comolia (Melastomataceae, Marcetieae) - Silva, Diego Nunes Da; Rocha, Maria José Reis Da; Maia, Vítor Hugo; Guimarães, Elsie Franklin; Guimarães, Paulo José Fernandes (Phytotaxa, 2021)
Comolia is a neotropical genus currently represented by 10 accepted species. Since the description of the genus, 47 names have been published within it. When investigating these names, we found that some of them needed to be typified. The aim of the present study was to provide the nomenclatural treatment for Comolia, including a list of all synonyms related to its species, typifications and nomenclatural comments, when necessary. Thirteen lectotypes and one neotype are designated here. Six names were lectotypified using two illustrations. In addition, we synonymized C. ovalifolia var. blanchetiana and C. ovalifolia var. denudata under C. ovalifolia, and we typified Melastoma rhexioides and exclude it from Comolia.